Game meat hygiene in focus microbiology, epidemiology, risk analysis, and quality assurance - International Research Forum on Game Meat Hygiene. Conference 2009 Brno, Czech Republic); Paulsen, P. (Peter).; SpringerLink (Online service). (Wageningen, the Netherlands Wageningen Academic Pub., 2011)
Game meat is consumed world-wide. In most regions, it contributes only a small part to the overall meat and food supply, but for reasons of animal welfare and sustainability it is sometimes considered an alternative to meat from farmed animals. Despite differences in game species, ante mortem conditions (free-range or fenced; wild or semi-domesticated), hunting or harvesting procedures and further handling of the carcass, there are common requirements as regards meat safety and quality. Whereas meat hygiene and safety have been an issue in game meat for export/import for a long time, primary production, domestic supply and direct supply to the consumer have recently been addressed by legislation and these sectors still present unresolved questions and challenges. This book combines 24 contributions presenting the view of experts in game meat hygiene and quality. They address four main topics: i.e. hygiene and microbiology, epidemiology, risk assessment and management and muscle biology and meat quality. In addition to contributions on this topic by authors from eight European countries, a South African perspective is provided, thus representing the standpoint of a major game meat exporter. This volume is the first in a series on safety and quality assurance along the game meat chain, following a from forest to fork approach and is targeted at scientists in academia and industry, graduate students as well as at governmental officials in veterinary public health and food safety.
Preface -- Section 1: Hygiene and microbiology -- Hygiene and microbiology of meat from wild game: an Austrian view -- Essential food safety management points in the supply chain of game meat in South Africa -- Game harvesting procedures and their effect on meat quality: the Africa experience -- Zoonotic diseases and direct marketing of game meat: aspects of consumer safety in Germany -- Dog bites in hunted large game: a hygienic and economical problem for game meat production -- Verocytotoxigenic Escherichia coli (VTEC) in wild ruminants in Germany -- Microbial quality of venison mean at retail in the UK in relation to production practices and processes -- Detection of Alaria spp. mesocercariae in game meat in Germany -- Hygiene management systems for commercial game harvesting teams in Namibia -- Salmonella spp. in wild boar (Sus scrofa): a public and animal health concern -- Preliminary results indicating game meat is more resistant to microbiological spoilage -- Section 2: Epidemiology -- Trichinellosis in wild and domestic pigs and public health: a Serbian perspective -- Influence of climate change on diseases of wild animals -- Dynamics of infectious diseases according to climate change: the Usutu virus epidemics in Vienna -- The utility of GIS in studying the distribution of Bovine Tuberculosis in wild boar (Sus scrofa) and red deer (Cervus elaphus) in Central Portugal. Section 3: Risk assessment and management -- Risk management of game: from theory to practice -- The monitoring of selected zoonotic diseases of wildlife in Lombardy and Emilia-Romagha, northern Italy -- Assurance of food safety along the game meat production chain: inspection of meat from wild game and education of official veterinarians and trained persons in Austria. Structure and legal framework for the direct local marketing of meat and meat products from wild game in Austria: the Lower Austrian model -- Approaches to game hygiene in the provice Belluno (Italy): from training to meat microbiology -- Section 4: Muscle biology and meat quality -- The muscle biological background of meat quality including that of game species -- Muscle biological and biochemical ramifications of farmed game husbandry with focus on deer and reindeer -- A summary of methods to access major physical-chemical and sensory quality traits of fresh (whole tissue) meat -- Evaluation of some parameters of post mortem changes of pheasant (Phasianus colchicus). Biographies of key contributors -- Index.
Electronic reproduction.
Keywords: Wildlife as food -- Safety measures -- Congresses; Meat hygiene -- Congresses; Food handling -- Congresses; Animals, Wild -- Congresses; Meat -- microbiology -- Congresses; Food Safety -- methods -- Congresses; Meat -- parasitology -- Congresses; Meat -- standards -- Congresses; Electronic books